Romandan Tiyatroya: Değirmen - Sarıpınar 1914 / From Novel to Theatre: Degirmen - Saripinar 1914 - Topçu, Hayrunisa (Journal of History Culture and Art Research, 2017)
Abstract Reşat Nuri Güntekin is one of the prolific author of Turkish Literature. He owns a lot of literary works within novel and theatre play genres. He cogitated about all components of theatre from decor, till play writer and he wrote many articles. His study on this field was continued by other authors in the following years. Turgut Özakman is a writer who, like Reşat Nuri, has been thought over play writing and studied on theoretical part of theater. The novel named Değirmen which was published in 1944 by Reşat Nuri, was adapted to theater by the name of Sarıpınar 1914 by Turgut Özakman. The play was first staged by Ankara Sanat Tiyatrosu on 16 February 1968. With the increasing interdisciplinary studies in recent years, the concept of adaptation has attracted the attention of researchers from almost every field. Therefore, the studies adapted from novel to theater have been discussed again with a new point of view. In this article named Romandan Tiyatroya: Değirmen / Sarıpınar 1914, Reşat Nuri’s novel Değirmen and Turgut Özakman’s theatre play Sarıpınar 1914 will be evaluated in the framework of the “adaptation theory”. It will be discussed the differences between the novel and theatre play and also reasons of the differences with the comparative evaluations made on the concept of plot, character, time and place. Öz Reşat Nuri Güntekin, Türk edebiyatının en üretken yazarlarından biridir. Özellikle roman ve tiyatro türünde birçok eseri vardır. Tiyatro konusunda dekordan oyun yazarlığına kadar her alanda kafa yormuş ve bu konuda birçok makale yazmıştır. Onun bu alanda yürüttüğü çalışmalar sonraki yıllarda başka yazarlar tarafından da devam ettirilmiştir. Turgut Özakman da tıpkı Reşat Nuri gibi oyun yazarlığı ile meşgul olmuş ve tiyatronun kuramsal kısmı üzerinde çalışmış bir yazardır. Reşat Nuri’nin 1944’te yayımlanan Değirmen isimli romanı, Turgut Özakman tarafından Sarıpınar 1914 adıyla tiyatroya uyarlanmıştır. Oyun ilk kez 16 Şubat 1968 tarihinde Ankara Sanat Tiyatrosu tarafından sahnelenmiştir. Son yıllarda disiplinler arası çalışmaların artmasıyla birlikte uyarlama kavramı neredeyse her alandan araştırmacıların dikkatini çekmektedir. Dolayısıyla romandan tiyatroya aktarılan eserler de yeni bir bakış açısıyla tekrar ele alınmaya başlanmıştır. Romandan Tiyatroya: Değirmen / Sarıpınar 1914 adlı makalede Reşat Nuri Güntekin’in Değirmen isimli romanı ve Turgut Özakman’ın Sarıpınar 1914 adlı tiyatro oyunu, “uyarlama kuramı” çerçevesinde değerlendirilecektir. Özellikle olay örgüsü, kişiler, zaman, mekân kavramları üzerinden yapılacak karşılaştırmalı değerlendirmelerle, iki eser arasındaki farklılıkların nedenleri ve bu farklılıkların uyarlanan eser üzerindeki etkileri tartışılacaktır.